2020
DOI: 10.31931/fmbc.v23i2.2020.124-133
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of a Common Freshwater Mussel, Amblema plicata, in a Southern U.S. River

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Additionally, Sheepnose are estimated to have lifespans of up to 30 years (Hove et al, 2015), such long‐lived species can also buffer populations from the loss of genetic diversity due to drift (Hoffman et al, 2017). If this is true, efforts and resources aimed at conservation strategies such as propagation and translocations would be better directed toward regaining habitat suitability and connectivity (Olson & Vaughn, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sheepnose are estimated to have lifespans of up to 30 years (Hove et al, 2015), such long‐lived species can also buffer populations from the loss of genetic diversity due to drift (Hoffman et al, 2017). If this is true, efforts and resources aimed at conservation strategies such as propagation and translocations would be better directed toward regaining habitat suitability and connectivity (Olson & Vaughn, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Uneven family size, as was observed in the produced juveniles in this experiment, can reduce Ne, so the population may be at risk of adverse effects (Ferguson et al 2013;Inoue, Aquarium, and Berg 2017;Jones, Neves, and Hallerman 2015). However, Olson and Vaughn (2020) found some genetic structure between upstream and downstream beds of Threeridge mussels in the Little River in Oklahoma. One other study also found genetic structuring within a river basin examining the Texas Hornshell mussel (Popenaias popeii) in the Black River of New Mexico (Inoue, Lang, and Berg 2015).…”
Section: Discussionmentioning
confidence: 51%
“…The source population was found to exhibit a deficit of heterozygotes. Ho to He ratios in the source population were comparable to nine Threeridge populations analyzed by Olson and Vaughn (2020) using the same set of microsatellite markers. Low levels of heterozygosity may be indicative of the relatedness of individuals in the source population, with potential occurrences of inbreeding (Harmon and Braude 2010).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation